Philodorema Essays in Greek and Roman Philosophy in Honor of Phillip Mitsis - Konstan, David (Parnassos Press - Fonte Aretusa, 2022)
In this wide-ranging volume of papers on Greek and Roman philosophy, a group of distinguished scholars has come together to honor Phillip Mitsis as a teacher, scholar, and colleague. Apart from examining a range of topics and philosophers that covers most areas of Classical philosophy and even beyond, the volume is particularly noteworthy for the variety of critical and philosophical methodologies it embraces. This reflects the honorand's belief that our understanding of philosophy and its relation to its own history must be continually re-examined and that such examinations inevitably benefit from the mutual engagement of different traditions and styles of philosophical argument, even when they seem to conflict. While not explicitly setting up methodological debates, the volume manages to intimate the benefits of more polyphonic discussions by showing eminent practitioners of various approaches going about their craft and presenting their arguments in the spirit of a friendly gift, or philodorema. Edited by David Konstan and David Sider, the volume collects essays in Ancient Greek and Roman Philosophy by Pietro Pucci, Gerasimos Santas, David Sider, Darren Gardner, Nathaniel Nicol, Heather L. Reid, Carlo DaVia, Theodore Scaltsas, David O. Brink, Fred D. Miller, Jr., Paul Schollmeier, Enrico Piergiacomi, David Konstan, Jean-Philippe Ranger, Paul A. Vander Waerdt, Joseph G. DeFilippo, Jon Miller, Brad Inwood, Paul T. Keyser, Christos C. Evangeliou, David Robertson, Michael Erler, and Alain Gigandet.